Peran Hakim Pengadilan Agama Kraksaan Dalam Meminimalisir Perkawinan Usia Dini - Sa'diyah, Nur Halimatus; Rusly, Fathullah; Firdausiyah, Vita (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
The minimum age of marriage is 19 years in Law Number 16 of 2019 concerning Marriage, which has an impact on the rampant application for marriage dispensation. This regulation should be a reference for the community in order to create an ideal and harmonious married life, but people tend to choose marriage dispensation even though it will have a negative impact on children's financial, psychological, and also children's health. The research aims to analyze the role of judges to minimize early marriage and judges' considerations to reject or approve applications for marriage dispensation, especially in the Kraksaan region. This article is classified as literature research with a qualitative approach. The methodology used is an empirical juridical study. The results of the study concluded that; The role of judges is very vital, especially in educating parents not to proceed with applications for marriage dispensation for the good of children.